PENGARUH RASIONALITAS EKONOMI DAN KELOMPOK TEMAN SEBAYA TERHADAP PERILAKU KONSUMSI MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Wahidah, Nurul; Asriati, Nuraini; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
ABSTRACTThis study examines some of the major effects of economic rationality and peer groups on the consumption behavior of FKIP UNTAN economics education education. A common problem in this study is